Experimental study on wave impulse and characteristic pressure of a vertical wall with overhanging horizontal cantilever slab. (1st December 2020) - Huang, Jianjun; Chen, Guoping
Abstract: Wave impact tests are carried out for a vertical wall with overhanging horizontal cantilever slab in a flume with the scale factor of 1:30. By setting various incoming wave conditions and structural elevations, different influences of wave height, wave period and clearance on the wave impulse and characteristic pressure are investigated. With the increasing of structural clearance, both wave impulse and characteristic pressure for cantilever slab and vertical wall show a firstly increasing and then decreasing trend, and reach the peak when clearance close to zero and 0.2 times wave height respectively. Besides, bigger wave steepness can induce larger wave impulse and characteristic pressure for the vertical wall. The relation between characteristic pressure and rise time present a smaller scatter, and has the almost similarity to that of impact pressure and rise time. Furthermore, a positive correlation between wave impulse and total duration is observed and the larger characteristic pressure is always corresponded to the bigger wave impulse. All the findings presented here may be used for future research as well as predesign. Highlights: Impulse and pressure firstly increase and then decrease with increasing clearance. Wave impulse attains the maximum when the clearance close to zero. Characteristic pressure reaches the peak when the clearance 0.2 times wave height. Relation between wave impulse and total duration of wave impact is proposed. Normalized relation between characteristic pressure and rise time is presented.